Molecular detection and characterization of Trichomonas spp. in wild birds in the Brazilian Pantanal - Pereira, Amanda Garcia [UNESP]; Simões, Sarah Raquel Jesus Santos [UNESP]; da Silva, Maitê Cardoso Coelho [UNESP]; Mariano, Leticia Colovatti [UNESP]; Calchi, Ana Cláudia [UNESP]; Cordova, Amir Salvador Alabi [UNESP]; Ferreira, Tiago Valadares; Pinho, João Batista; Fecchio, Alan; Bassini-Silva, Ricardo; Castro-Santiago, Ana Carolina; Bell, Jeffrey; et al. (FapUNIFESP (SciELO), 2025)
Members of the family Trichomonadidae, particularly Trichomonas gallinae, are globally distributed avian parasites that primarily infect birds from the orders Columbiformes, Falconiformes, and Strigiformes. Although infections in Passeriformes are often subclinical, clinical cases have been reported. Transmission occurs through direct contact or indirectly via contaminated food or water, enabling infection across various avian orders, including Anseriformes, Falconiformes, Galliformes, Gruiformes, Passeriformes, Piciformes, Psittaciformes, and Strigiformes. This study aimed to assess the occurrence and genetic diversity of Trichomonas spp. in 246 wild birds captured in Poconé, Mato Grosso, located in the Brazilian Pantanal. Oropharyngeal swab samples were collected in July 2022 from birds belonging to six different orders. Following DNA extraction, molecular detection was performed targeting the ITS1/5.8S/ITS2 ribosomal region. Of the total samples, 107 (43.5%) tested positive, with high prevalence in Passeriformes (40.8%), Cuculiformes (75%), and Columbiformes (63.2%). Phylogenetic analysis using Bayesian inference placed the 18 obtained sequences, representing five distinct haplotypes, into three separate clades of T. gallinae. In conclusion, Trichomonas DNA was detected in asymptomatic birds from three different avian orders. The high infection prevalence and haplotype sharing among species highlight the widespread distribution and potential transmission of T. gallinae among wild birds in the Brazilian Pantanal.